Blumgart method using LAPRA-TY clips facilitates pancreaticojejunostomy in laparoscopic pancreaticoduodenectomy. Issue 10 (March 2020) - Nagakawa, Yuichi; Takishita, Chie; Hijikata, Yosuke; Osakabe, Hiroaki; Nishino, Hitoe; Akashi, Masanori; Nakajima, Tetsushi; Shirota, Tomoki; Sahara, Yatsuka; Hosokawa, Yuichi; Ishizaki, Tetsuo; Katsumata, Kenji; et al.
Abstract : Abstract: The modified Blumgart method for pancreaticojejunostomy has been shown to reduce the rate of postoperative pancreatic fistula (POPF) in open surgery. We describe a modified Blumgart method using LAPRA-TY suture clips to facilitate laparoscopic pancreaticojejunostomy. We prepared a double-armed 4-0 nonabsorbable monofilament, which was ligated using the LAPRA-TY clip at the tail end, 12-cm in length. Next, the U-suture was placed through the pancreatic stump and the seromuscular layer of the jejunum. We performed duct-to-mucosa suturing with a 5-0 absorbable monofilament. After completing the duct-to-mucosa suturing, as a final step we placed the sutures through the seromuscular layer of the jejunum on the ventral side and tightly secured the thread with the LAPRA-TY clips. We performed laparoscopic Blumgart pancreaticojejunostomy during pancreaticoduodenectomy in 39 patients. We compared the surgical outcomes of 19 patients who underwent Blumgart pancreaticojejunostomy using the LAPRA-TY clips (LAPRA-TY group) with 20 patients undergoing surgery not using the LAPRA-TY clips (conventional group). The rate of clinically relevant postoperative pancreatic fistula in the LAPRA-TY group was 21.1%, which did not differ significantly from the rate of the conventional group. However, the mean time of pancreaticojejunostomy in the LAPRA-TY group was 56.2 min (range, 39–79 min), which was significantly shorter than that of the conventional group (69.7 min; range, 53–105 min, P < .001). Although the modified Blumgart pancreaticojejunostomy using LAPRA-TY suture clips did not improve the pancreatic fistula rate, it allowed for shorter operative times. Thus, this procedure lends itself to positive surgical and patient outcomes.